Pastors, partners, and paternalists : African church leaders and western missionaries in the Anglican Church in Kenya, 1850-1900 - Reed, Colin. (Studies in Christian Mission, 1997)
A study tracing the relationships between missionaries and African Church workers in Kenya in the years 1850-1900, as missionaries increasingly adopted imperial assumptions of Western superiority. It tells the story of the first Anglican clergy in Kenya, their wives and colleagues; their rescue from slavery, their education in India and their subsequent work in East Africa. It demonstrates their contribution to the rapid growth of the Church and of indigenous Christian communities. Yet later missionaries were not willing to accord to the Africans the position they had a right to expect. The book recounts their protest and the development of a Church order. Similar events in West Africa have been documented, but this is the first time such a pattern in East Africa has been outlined.